2022
DOI: 10.3389/fmars.2022.974967
|View full text |Cite
|
Sign up to set email alerts
|

Differences and similarities in the phytoplankton communities of two coupled transitional and marine ecosystems (the Lagoon of Venice and the Gulf of Venice - Northern Adriatic Sea)

Abstract: The main aim of this paper is to paint an ecological picture of the phytoplankton communities of two adjacent and connected ecosystems, one transitional and one coastal marine, in the Northern Adriatic Sea: the Lagoon of Venice (LoV) and the Gulf of Venice (GoV). Based on 10 years (2011-2020) of monthly samplings, we compare the taxonomic composition, abundance and seasonal cycles of the two ecosystems. We focus on the inner zones of the LoV and on the coastal sea up to 8 nmi offshore, an area suitable for ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 73 publications
2
15
0
Order By: Relevance
“…Moreover, these studies suggested meso-oligotrophic conditions for the system by considering the rate at which nutrients were renewed in the water column [ 22 , 43 ]. Our data confirmed these findings and demonstrated that the Aquatina Lagoon is still a highly productive ecosystem today, like other transitional Mediterranean systems [ 4 , 9 , 10 , 11 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Moreover, these studies suggested meso-oligotrophic conditions for the system by considering the rate at which nutrients were renewed in the water column [ 22 , 43 ]. Our data confirmed these findings and demonstrated that the Aquatina Lagoon is still a highly productive ecosystem today, like other transitional Mediterranean systems [ 4 , 9 , 10 , 11 ].…”
Section: Discussionsupporting
confidence: 89%
“…The seasonal trend of phytoplankton showed large fluctuations on an annual cycle, driven both by the seasonal rhythm and by the pulse of nutrients (mainly nitrite plus nitrate). The maximum of the total autotrophic biomass was recorded in summer, as has already been described for other temperate transitional systems, such as the Venice Lagoon [ 10 , 11 ], which are characterized by shallow depths and permanently high nutrient levels [ 44 , 45 ]. On the contrary, the phytoplankton dynamics in the Aquatina Lagoon differed from those observed in other Apulian brackish environments.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In coastal lagoons, the combination of local and regional anthropogenic and natural forcings, land-ocean connectivity, strong benthic-pelagic coupling, relative confinement, complex hydrodynamics, and high habitat diversity increases the intricacy of the forces acting on phytoplankton assemblages [16,32]. This intrinsic complexity of coastal lagoons promotes variable patterns of phytoplankton change over time [33][34][35] and high spatial heterogeneity, both across [36][37][38] and within lagoons [10,21,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%